Enhancing English Proficiency for Filipinos Through a Multimedia Approach Based on Constructivist Learning Theory - Sasan, John Michael (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to explain Filipinos' English language proficiency through a Multimedia Approach Based on Constructivist Learning Theory. This research is qualitative with a library research approach. The research data is in the form of Filipino English language proficiency with data sources accessed from several recent journal studies. Data collection techniques using documentation. While data analysis with content analysis techniques. The research results show in the context of English study, multimedia has provided learners with unique features and benefits. Constructivist learning theory, on the other hand, has had a considerable impact on students' learning processes and progress as one of the most fundamental teaching theories in the field of education. This study looks at a wide range of sources to support the claim that integrating multimedia and constructivism theory improved students' overall English learning experience. While the authors of this study thought it would help students improve their English learning, they also wanted to give teachers a better method to help them reduce stress in the classroom while still providing an effective teaching-learning process.